Novel control and detection strategies for porcine viruses - Khanal, Pratiksha (Kansas State University, 2023)
Pork is the most widely consumed animal protein globally. Viral diseases affecting pork production have a major socio-economic impact on pork producers around the world. Novel techniques to prevent and control the spread of viral swine diseases are necessary to guard swine health and ensure global food security. African swine fever virus (ASFV) is a current threat to global pork production due to its high case fatality rate, lack of commercial vaccine, recent transboundary spread into new regions of the world, and challenges of virus control. ASFV causes a severe hemorrhagic disease characterized by high fever, loss of appetite, hemorrhage, and depression. Pigs infected with highly virulent ASFV strains frequently die within 2 weeks with up to 100% mortality rates. Economic losses due to the introduction of ASFV into the United States (US) are estimated to be $15 billion if disease control allows the US to reenter export markets within two years. Over $50 billion in losses could occur if the disease spreads to the feral swine population and the US is unable to eliminate the disease over a ten-year period. Thus, preventing introduction and further spread of ASFV is critical for the US and any country currently negative for the virus. Feed ingredients used in US commercial swine diets are sourced in large volumes from countries currently positive for the virus. ASFV has been shown to be stable in feed ingredients subjected to transoceanic conditions and transmission can occur through the natural consumption of contaminated feed. Despite evidence supporting the role of feed in ASFV introduction risk and transboundary spread, diagnostic tools for surveillance and detection of ASFV in feed remains an industry challenge. Porcine reproductive and respiratory syndrome (PRRS) has the highest economic impact on swine production in the US, with estimated annual losses to the US pork industry at $663.91 million. It is caused by PRRS virus (PRRSV), a single-stranded RNA virus belonging to the family Arteriviridae. The major economic impact of PRRS on the global swine industry is due to diminished weight gain and respiratory disease in growing pigs (Holtkamp et al., 2013). PRRSV is frequently isolated along with porcine circovirus type 2 (PCV-2) in US field cases. PCV-2 is a single-stranded DNA virus belonging to the family Circoviridae. It is associated with a group of disease syndromes termed porcine circovirus-associated disease (PCVAD), characterized by muscle wasting, respiratory disease, jaundice, or pallor, and reduced weight gain in growing pigs. PRRSV and PCV-2 both cause systemic infections primarily targeting pulmonary and lymphoid tissue and can be used in co-infection models to reproduce PCVAD experimentally. Co-infection with these two viruses modulates host immunity resulting in increased viral replication and enhanced polymicrobial disease compared to single infections alone. Recent research has shown that the gut microbiome, or collection of microorganisms living in the gastrointestinal tract, is associated with vaccine efficacy and health outcomes following PRRSV infection in pigs. Moreover, the gut microbiome is known to play an essential role in local and systemic immunity and that gut microbiome-based therapeutics such as fecal microbiota transplant (FMT) have therapeutic and prophylactic potential for diseases outside the gastrointestinal system. This dissertation includes four research studies to investigate novel control and detection strategies for porcine viruses. The objective of the first study was to evaluate feed dust as a novel diagnostic sample type for the detection of ASFV nucleic acid and infectious titer in experimentally contaminated feed. Moist swabs were used to collect dust from creep feeders after natural consumption of feed inoculated with 3.1–5.4 log₁₀ TCID₅₀/g ASFV Georgia 2007 in the presence and absence of antimicrobial feed additives. ASFV DNA was detectable by qPCR in feed dust for at least 8 h after feed inoculation and in the presence of antimicrobial feed additives. Virus isolation could detect infectious ASFV in feed dust when swabbed 30-min post-inoculation. Overall, this study provides valuable proof of concept data on feed dust as a potential surveillance tool for ASFV in contaminated feed and ingredients. The objective of the second study was to investigate the effects of PRRS MLV vaccination on the gut microbiome composition and diversity of nursery pigs. At twenty-eight days post-vaccination, fecal samples were collected from both vaccinated (n = 12) and nonvaccinated (n = 12) pigs. Gut microbiomes were compared between the two groups using the Lawrence Livermore Microbial Detection Array (LLMDA). Vaccinated pigs had increased microbial species diversity and increased Firmicutes to Bacteroidetes ratio. Significant differences were also noted in microbiome composition at different taxonomic levels. Specifically, the Enterobacteriaceae family was detected at a significantly higher rate in vaccinated pigs compared to nonvaccinated pigs. Overall, these results suggest that infection with PRRS MLV may modulate the gut microbiome and that certain microbiome characteristics may contribute to vaccine efficacy. The objective of the third study was to characterize the FMT material through several approaches, including the identification of antibiotic (ABx) resistance genes, evaluate the bacterial species cultivability, and determine concentration of culturable microorganisms. A total of 26 bacterial isolates were identified by mass spectrometry out of which 24 isolates were culturable. Overall, the study shows that FMT material can be characterized and pure cultures of cultivable fecal bacteria can be obtained using culture-based techniques, and the cultivable portion of the FMT material is dominated by anaerobes. The objective of the fourth study was to develop a microbiota therapeutic with a pre-defined consortium of cultivable microbes isolated from the FMT material shown to be associated with improved health outcomes in growing pigs with PCVAD. This study aimed to investigate the efficacy of the cultivable microbiota therapeutic as a means to improve disease outcomes following PRRSV and PCV-2d co-infection. Pure cultures of 24 bacterial species were pooled together in sterile normal saline with 10% glycerol mimicking their composition in the fecal transplant material. One group of pigs (n = 50) was administered the microbiota therapeutic while a control group (n = 50) was administered a sterile mock transplant. All pigs were co-infected with PRRSV and PCV-2 after 7 days of the therapeutic administration. Microbiota therapeutic appeared safe as no adverse effects were noted in transplanted pigs, increased average daily gain of transplanted pigs prior to co-infection (-8 to 0 dpi) and in the late stage of co-infection (38 to 42 dpi). However, microbiota therapeutic largely failed to replicate the overall benefits of FMT in PCVAD affected pigs. Taken together, the dissertation provides insights into a novel diagnostic sample for ASFV detection in swine feed and proposes novel methods to reduce PRRS associated losses including modulating pig gut microbiome to improve PRRS MLV vaccine efficacy and developing and utilizing a pre-defined microbial consortium to improve or aid current therapies for PCVAD.
Keywords: Porcine viruses; Gut microbiome; Novel diagnostic tools; Novel control measures; African swine fever; Porcine reproductive and respiratory syndrome